Efektivitas Program Membangun Keluarga Utama sebagai Program Pemberdayaan Masyarakat Islami (Studi Kasus di KSPPS BMT Tumang) - M. Qoshid Al Hadi (Jurnal Studi Agama dan Masyarakat, 2019)
Poverty alleviation is a development general agenda all over the world, including Indonesia. Quality and sustainable development is the development capabling of empowering people to alleviate poverty and improve quality of life. The Program of Main Family Building  (MKU) initiated by the Indonesian BMT Association (PBMTI) is a new idea as an effort of  Baitul Maal wa Tamwil (BMT) to be involved in empowerment programs, especially family. The MKU program launched since 2014 needs to be evaluated to find out how effective the program is. This research focuses on program identification through four indicators of effectiveness, namely the accuracy of targets, socialization, objectives and monitoring program. This study uses a quantitative approach by distributing questionnaires to 32 respondents consisting of all MKU program members. The finding revealed that the MKU program implemented by the KSPPS Tumang BMT showed sufficient effectiveness or 72.7% effective.